Investing in statistical programs and artificial intelligence in weather and climate applications in Iraq (Journal of the College of Basic Education, 2026)
Modern statistical techniques, programs, and artificial intelligence applications are used to provide a clear and accurate model of the atmospheric layers for weather and climate analysis. Various environmental factors, such as temperature, atmospheric pressure, wind, clouds, and turbulence in air movement, all affect the general properties of the thermal inversion layer, which in turn affects the general properties of radiative surface thermal inversion and upper thermal inversion. For such studies, it is necessary to utilize these modern applications and work on developing them. The importance of this research was highlighted in these statistical applications and programs. As an example, a statistical program was developed in Iraq and applied to the Baghdad station. We take the Skew-T program to plot daily radiosonde data. It is one of four thermodynamic diagrams commonly used in weather analysis and forecasting. By adding statistical models, With the Basic program which contains 21 statistical analysis modules (Analytic Module, Fronts and Forecast Module) the main use of this logarithmic chart is to plot radiosonde data which gives a vertical picture of temperature, dew point, atmospheric pressure, altitude, wind speed and direction, for the entire troposphere and lower stratosphere.